Effects of Sound, Vocabulary, and Grammar Learning Aptitude on Adult Second Language Speech Attainment in Foreign Language Classrooms. Issue 3 (27th June 2017) - Saito, Kazuya
Abstract: This study examines the relationship between different types of language learning aptitude (measured via the LLAMA test) and adult second language (L2) learners' attainment in speech production in English‐as‐a‐foreign‐language (EFL) classrooms. Picture descriptions elicited from 50 Japanese EFL learners from varied proficiency levels were analyzed through a range of pronunciation, fluency, vocabulary, and grammar measures. Results indicated that the learners' aptitude test scores in phonemic coding, rote and associative memory, and language analytic ability were moderately associated with the phonological/morphological accuracy, fluency, and lexicogrammar complexity of production, which are linguistic aspects thought to be instrumental in the acquisition of advanced L2 oral ability. In contrast, aptitude–proficiency links were not found with respect to relatively implicit and incidental learning aptitude (sound recognition) and foundational aspects of proficiency (appropriate use of frequent words). Open Practices: This article has been awarded an Open Materials badge. All materials are publicly accessible in the IRIS digital repository athttp://www.iris-database.org . Learn more about the Open Practices badges from the Center for Open Science:https://osf.io/tvyxz/wiki .